Analisis Tingkat Kesehatan PT. Bank Mega Syariah Periode 2020-2024 - Umiyati Umiyati; Salwa Maulydya; Muhammad Haikal Baihaki; Rivarilla Alysha (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
The purpose of this study is to evaluate the financial performance of PT Bank Mega Syariah during the 2020–2024 period using an integrated approach that includes the RGEC method, efficiency analysis using Data Envelopment Analysis (DEA), the Z-score to measure financial stability, and the Altman Z-Score model to predict the likelihood of a financial crisis. This method was chosen to provide a comprehensive overview of the bank's health, including risk and profitability, operational efficiency, financial resilience, and the likelihood of bankruptcy. The quantitative method used in this study is derived from secondary data collected from Bank Mega Syariah's annual financial statements and Good Corporate Governance (GCG) reports for the past five years. Financial ratio calculation methods and relevant statistical models were used to process and analyze all data. The results show that the bank's risk profile is very healthy; the continuously decreasing Non-Performing Financing (NPF) Ratio and the Financing to Deposit Ratio (FDR) Ratio that remains in the healthy category indicate this. GCG has consistently been ranked Good, with an increase in the second half of 2023. Both ROA and ROE have changed, but remain within the range reflecting profitable performance. With a high CAR, the bank has strong capital capacity to cover potential risks. Bank Mega Syariah demonstrates a full level of efficiency in the DEA analysis, and its Z-score indicates that the bank is in a very safe position.